PROBABILITIES OF PHYSICAL LINK BETWEEN THE COMPONENTS OF THE SELECTED MULTIPLE SYSTEMS FROM WDS CATALOG - Maigurova, N. V.; Protsyuk, Yu. I. (Одеські астрономічні публікації, 2019)
Astrometric CCD observations of visual components of double and multiple stars were performed using the RI MAO Axial Meridian Circle (AMC) with new Apogee Alta AI-F8300 CCD camera mounted at the telescope in 2018. Observations were carried out automatically in drift- scan mode using a standard R filter. Objects for observational program were selected from the Washington Double Star Catalog (WDS). During the 23 nights, 983 observations of 579 double and multiple systems from the WDS catalog were obtained. Astrometric reductions of the observations showed high accuracy, with an average error of one position about 0.1" in right ascension and declination for stars up to 16 mag , which were observed more than 3 times. The purpose of our study was to measure the parameters of the mutual configuration of pairs from the original images and to draw some conclusions about the physical connection of the components in the selected systems. The measurement array that will be sent to the WDS database includes values of positional angle, angular separation, stellar magnitude difference, and epoch of the observation. A detailed analysis of the pairs of stars in the selected 5 systems to clarify their composition and the nature of the link between them was made. Positional data from the Hipparcos, Tycho2, UCAC4, Gaia DR2, and Pan-STARRS (PS1) catalogs were used as sources of additional information about the investigated stars. The search for possible invisible stars in the selected systems was performed using the statistical Wielen method, based on the analysis of the differences of instantaneous and long-term averaged proper motions of the stars. The proper motions of the space Gaia DR2 catalog were considered to be instantaneous, the long-term averaged proper motions were used from Tycho-2 and UCAC4 catalogs. Obtained values of the statistical parameter in some cases indicate a high probability of existence of invisible close components in the studied systems. Detailed comments of the results for each of the selected systems are provided.